Mental illness and pulmonary tuberculosis: a bidirectional two-sample Mendelian randomization study - Chen, Xing; Yang, Fengbo; He, Ronghui (Frontiers in Psychiatry, 2024)
Background: Observational studies have confirmed that mental illness and pulmonary tuberculosis are closely related and increase each other's incidence; however, whether there is a causal genetic association between the two diseases remains unknown. We attempted to answer this question using bidirectional two-sample Mendelian randomization (MR) in a large cohort study.We performed a bidirectional MR analysis between mental illness (major depressive, anxiety disorder, bipolar disorder, and schizophrenia) and pulmonary tuberculosis using summary statistics from genome-wide association studies in European individuals. The inverse-variance weighted method was used as the primary analytical method to assess causality. In addition, other additional MR methods (weighted median, MR-Egger, and weighted mode) were used to supplement the inverse-variance weighted results. Furthermore, several sensitivity analyses were performed to assess heterogeneity, horizontal pleiotropy, and stability.We identified no causal genetic association between mental illness and pulmonary tuberculosis after applying the inverse variance weighted method (major depressive: odds ratio (OR) = 1.00, 95% confidence interval (CI) = 0.59-1.